Mapping dispositions for social justice: towards a cartography of reflection. Issue 3 (3rd May 2016) - Casebeer, Daniel
Abstract: As non-White students now outnumber their White counterparts in America's public schools, it is important for teacher education programs, which graduate a predominantly White cadre of teachers, to focus on the development of dispositions for social justice. When teachers view cultural diversity as a problem, they risk developing erroneous expectations for their students, which can support the surreptitious insertion of prejudices into the latent curriculum. In order to help preservice teachers reflect on their understanding of diverse perspectives, especially those related to cognitive complexity, this study uses social cartography and discourse analysis to map their dispositions. Discussion and self-reflection lead to understanding and self-monitoring, and mapping can help teacher candidates identify those areas in which they may harbour apathetic worldviews or unifocal perspectives.